Molecular identification of cryptic cysticercosis: Taenia ovis krabbei in wild intermediate and domestic definitive hosts. Issue 2 (28th March 2017) - Formenti, N.; Chiari, M.; Trogu, T.; Gaffuri, A.; Garbarino, C.; Boniotti, M.B.; Corradini, C.; Lanfranchi, P.; Ferrari, N.
Abstract: The complex life cycle of taeniids represents an ideal model of a multi-host system. The complexity of these parasites can therefore cover the epidemiological issues of the interface between wild and domestic animals, especially once spatial overlap between wild and domestic definitive and intermediate hosts occurs. Here we use the occurrence of Taenia ovis krabbei in two model areas as an example of this epidemiological complexity. In two contiguous areas in the Italian northern Apennines, two hunted roe deer ( Capreolus capreolus ) showed numerous cysticerci in the muscles of their whole body and an adult tapeworm was recorded in a semi-stray dog ( Canis lupus familiaris ). Through molecular typing of the mitochondrial cytochrome c oxidase I ( cox1 ) gene, cysticerci and the adult tapeworm of T. krabbei were identified. Taenia krabbei cysticercosis was recorded for the first time in Italy. Although the role of dogs in the parasite's life cycle emerges, the overlap between wild and domestic definitive hosts and the increase of wild population densities raise concerns about the temporal (old or new) introduction and the spread of this parasite by one of these canid species (wolf ( Canis lupus ) or dog). Although T. krabbei is not a public health issue, economic concerns emerged for hunters and meat producers, related to the damage of carcasses by cysticerci. Therefore, there is a need to evaluate the spread of T. krabbei in the intermediate and definitive host populations, and to ensure the relevant sanitary education for hunters in order to avoid practices that could favour the spread and maintenance of its life cycle.